2022
DOI: 10.15639/teflinjournal.v33i1/148-172
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of L2 Pragmatic Autonomous and Controlled Motivations on Engagement With Pragmatic Aspect

Abstract: No study has investigated the relationship between student engagement per se and student motivation within second language (L2) pragmatics, notwithstanding the significance of engagement for L2 learning. The present study aimed to explore the effects of two global motivational orientations (autonomous and controlled motivations) on behavioral engagement within the perspective of L2 pragmatics by drawing on self-determination theory. A total of 76 college students agreed to participate and were requested to fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…This, as hypothesized, facilitates the pragmatic development of EFL learners. These conclusions align with those of Sanjaya et al (2022), where a standard multiple linear regression demonstrated that both autonomous and controlled motivations significantly contributed to the variance in pragmatic engagement. The current study expands upon this previous work by providing empirical evidence of the interaction between proficiency and L2 motivation in pragmatic engagement.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This, as hypothesized, facilitates the pragmatic development of EFL learners. These conclusions align with those of Sanjaya et al (2022), where a standard multiple linear regression demonstrated that both autonomous and controlled motivations significantly contributed to the variance in pragmatic engagement. The current study expands upon this previous work by providing empirical evidence of the interaction between proficiency and L2 motivation in pragmatic engagement.…”
Section: Discussionsupporting
confidence: 87%
“…The coefficients were .85 for intrinsic motivation, .91 for identified motivation, .84 for introjected motivation, and .83 for external motivation. The internal consistency of the engagement scale was .90 (Sanjaya et al, 2022). These reliability estimates exceeded the minimum acceptable reliability coefficient of .70, demonstrating the internal consistency of the overall scales.…”
Section: B Instrumentsmentioning
confidence: 74%
See 2 more Smart Citations
“…In terms of empathetic attitude, empathetic people show greater intrinsic motivation than non-empathetic or indifferent people, similar to what has been obtained in other studies in which they pointed out motivation as a relevant factor in the development of empathy, related to the "individual stage of development linked to the human quality of each student". All this is related to the initial motivation that prompted students to enrol in a university education [38,60,63].…”
Section: Discussionmentioning
confidence: 99%